Targeting the menaquinol binding loop of mycobacterial cytochrome bd oxidase - Harikishore, Amaravadhi (2020)
Mycobacteria have shown enormous resilience to survive and persist by remodeling and altering metabolic requirements. Under stringent conditions or exposure to drugs, mycobacteria have adapted to rescue themselves by shutting down their major metabolic activity and elevate certain survival factor levels and efflux pathways to survive and evade the effects of drug treatments. A fundamental feature in this adaptation is the ability of mycobacteria to vary the enzyme composition of the electron transport chain (ETC), which generates the proton motive force for the synthesis of adenosine triphosphate via oxidative phosphorylation. Mycobacteria harbor dehydrogenases to fuel the ETC, and two terminal respiratory oxidases, an aa3-type cytochrome c oxidase (cyt-bcc-aa3) and a bacterial specific cytochrome bd-type menaquinol oxidase (cyt-bd). In this study, we employed homology modeling and structure-based virtual screening studies to target mycobacteria-specific residues anchoring the b558 menaquinol binding region of Mycobacterium tuberculosis cyt-bd oxidase to obtain a focused library. Furthermore, ATP synthesis inhibition assays were carried out. One of the ligands MQL-H2 inhibited both NADH2- and succinate-driven ATP synthesis inhibition of Mycobacterium smegmatis inside-out vesicles in micromolar potency. Similarly, MQL-H2 also inhibited NADH2-driven ATP synthesis in inside-out vesicles of the cytochrome-bcc oxidase deficient M. smegmatis strain. Since neither varying the electron donor substrates nor deletion of the cyt-bcc oxidase, a major source of protons, hindered the inhibitory effects of the MQL-H2, reflecting that MQL-H2 targets the terminal oxidase cytochrome bd oxidase, which was consistent with molecular docking studies.